Factors Determining the Characteristics of Cocoa Soil in Sulawesi - Erwin Prastowo; John Bako Baon (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2020)
Sulawesi exhibits unique land characteristics as a result of complex geological and geomorphological processes. The information related to what extent of theseprocesses affect regional soil characteristics is still limited. An investigation was performed on cocoa farms from three major cocoa producers, i.e. South Sulawesi, Central Sulawesi, and Southeast Sulawesi. A research was done to point out the key variables contributing to cocoa soil characteristics. Soil survey was performed based on available local information to collect top soil composite samples, i.e. 0–30 cm depth, in the circle of cocoa stand within 50–75 cm radius. A routine soil analysis was done to evaluate soil texture, organic carbon (C), total nitrogen, K, Ca, Mg, soil pH (H2O), and some micronutrients, i.e. Fe, Cu, and Zn. To simplify the complexity, the multivariate data was submitted into principal component analysis (PCA). Additional mapping of soil variable gradient through inverse distance weighting (IDW) interpolation was included in the analysis to improve our interpretations. Data show that the variability for almost all investigated variables is high with coefficient of variation (CV) of up to about 118% for Fe. While low variability with CV about 10% was observed for soil pH (H2O). The PCA demonstrates that the first five principal components (PCs) account for 56.89% of variance in the original variables. Two factors to be considered to explain the variation in the PCs was soil texture and parent material. Further analyses exhibit an association of sand, silt, and clay fractions to Southeast, Central, and South Sulawesi. Mineral compositions, such as K, Ca, Mg, Fe, and Zn, exhibit an important contribution to the parent material factor as they define the variability in the PCs. Additionally, the analysis of gradient maps may indicate the two physical environmental conditions, i.e. landform and geological setting, contribute to the specific characteristics of cocoa soil.